Exploring behavioral drivers of tax compliance: The mediating role of attitude and moral value - Oktavianti, Oktavianti; Tibrani, Tibrani; Salesti, Jayana (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
Tax compliance remains challenging for the government due to the interconnection of economic, social, cultural, and perceptual elements that harm taxpayer behavior. This study aims to investigate the influence of behavioral drivers on tax compliance, focusing on attitudes and moral principles as mediators. A quantitative technique was used to survey 265 taxpayers in Riau Islands Province. Structural equation modeling (SEM-PLS) was used to investigate relationship between variables. The results demonstrate BC exerts a direct and significant influence on MV and ATT, while also exhibiting a positive correlation in bootstrapping tests or via the median variable with TC. The correlation between BC and TC is statistically insignificant. This result is noteworthy, as the cognitive dimensions of tax behavior—specifically morality and attitude—are more significant in influencing taxpayer behavior regarding tax compliance levels. It is crucial to highlight subjective perceptions in creating a favorable environment for taxpayers. This research theoretically enhances behavioral-based tax compliance model by incorporating psychological and ethical aspects. The findings indicate that tax authorities should formulate policies and campaigns that foster positive attitudes and improve moral responsibility, alongside traditional law enforcement, to augment voluntary compliance and fortify the tax system.